PENGARUH KUALITAS PELAYANAN, PERSEPSI HARGA DAN TINGKAT KEPERCAYAAN KONSUMEN TERHADAP LOYALITAS PELANGGAN STUDI KASUS PADA MASKAPAI SUSI AIR CILACAP - Rustina Dewi Werdiasih (JURNAL EKONOMI, 2020)
The purpose of this study is to aim and partially analyze the effect of service quality, price perception and level of consumer trust on customer loyalty, analyze together the effect of service quality, price perception and level of consumer confidence on customer loyalty and analyze variables that have a dominant influence on customer loyalty at Susi Air Cilacap Airlines.The sample used was 52 people drawn from a population of 109 people. The research instrument used questionnaires arranged on a scale of 1-5, a score of 1 for strongly disagree responses and a score of 5 for strongly agreed responses. The analysis technique used is descriptive analysis and multiple regression analysis. The hypotheses used in this study are: (1) The service quality variable has a significant effect on customer loyalty on the Susi Air Cilacap airline. (2) Variable price perception significantly influences customer loyalty on Susi Air Cilacap airline. (3) The variable level of consumer confidence has a significant effect on customer loyalty on the Susi Air Cilacap airline. (4) Variable service quality, price perception and level of consumer trust together affect customer loyalty on the Susi Air Cilacap airline. (5) The variable of the level of consumer confidence is the most dominant influence on customer loyalty on the airline Susi Air Cilacap.To find out the magnitude of the effect of service quality, price perception and level of consumer confidence on customer loyalty on the airline Susi Air Cilacap used multiple linear analysis. To test the effect simultaneously used the F test with degrees of freedom (df) = k and (n-k-2) with a confidence level of 5% (Î± = 0.05).Based on the results of the T-test the variable of service quality obtained value of tcount> ttable ie 2.080> 1.6765 hypothesis is accepted. Price perception variable obtained by t count> t table that is 2.770> 1.6765 hypothesis is accepted. The variable of consumer confidence obtained by tcount> ttable is 1.918> 1.6765 and is accepted. The results of the analysis obtained fcount> ftabel is 5,319>2.79. And the most dominant variable influencing customer loyalty is the consumer confidence hypothesis is rejected. Because the most dominant variable is price perception.The conclusion of this study, based on the results of the study the most dominant variable affecting customer loyalty is the perception of prices with a beta coefficient (2.770) greater than service quality (2,080) and consumer confidence (1,918). Rsquare coefficient value of 24.9% customer loyalty variables can be explained by the variable service quality, price perception and level of consumer confidence, while 75.1% is explained by other variables outside this study.Keywords: Service quality, Price perception, Level of consumer trust, Customer loyalty.